An overview on performance characteristics of bio-jet fuels. (1st February 2019) - Yang, Jie; Xin, Zhong; He, Quan (Sophia); Corscadden, Kenneth; Niu, Haibo
Abstract: Bio-based aviation fuels are considered as a promising alternative for conventional aviation fuels due to their sustainability and environmental friendliness. This review evaluated bio-jet fuels' performance based on their physicochemical properties, including low-temperature fluidity, thermal oxidation stability, combustion property, fuel compatibility and volatility, and energy density. The objective is to understand the effects of the chemical compositions of bio-jet fuels on their performance characteristics. This is of particular importance in that bio-jet fuels are generally derived from a broad spectrum of feedstock and thus have very different composition. In general, bio-jet fuels exhibit satisfactory characteristics in compliance with the American Society for Testing and Materials D7566-18 standard. The aromatic content has a critical influence on the performance of bio-jet fuels. Research efforts are needed to study the characteristics of recently certified bio-based blending components such as synthesized iso-paraffins and alcohol-to-jet. Storage stability, a rarely reported property also deserves further investigation.